Biblioteca pública - barrio Rumipamba - Jácome Vanegas, Priscila Elizabeth (2019)
In the last decades the Metropolitan District of Quito has had an expansive and accelerated growth that has led to an occupation without limits in the peripheries and the valleys of the city. The irrational expansion has created a fragmented city with scattered and segregated functions, loss of public space and social cohesion, environmental pollution and, finally, poorly populated neighborhoods. In the case of Av. 10 Agosto the problem is evident, the neighborhoods have been conforming at the expense of the road network, giving the car higher priority causing chaos in the nodes of the city or appropriating the public space, which, in addition, caused high levels of gases and noise therefore has become an access road, public spaces are residual and of poor quality, activities are mono-functional and segregated according to the "exclusivity" and economy of the sector, while other neighborhoods are forgotten and not very dynamic. The New Urban Plan for Av. 10 de Agosto generated by the Workshop of Projects VII, proposes an integral proposal accompanied by four main axes: public space, mobility, levels of occupation of land and equipment. In the case of the Rumipamba neighborhood located in the north-side of Quito, the creation of a public library that could be a support for education and knowledge of society is proposed. The library intends to create a link between knowledge and praxis. On one hand, revaluing the book as an important source for educational development at the same time to implement new activities with technological material. The architectural object bases its design on three fundamental aspects: light, circulation and public space.